函数[img=216x83]1802dbe9cf6bc43.png[/img]的反函数是( )。
A: [img=265x83]1802dbe9d991653.png[/img]
B: [img=241x83]1802dbe9e3d07e7.png[/img]
C: [img=250x83]1802dbe9ee13f79.png[/img]
D: [img=261x83]1802dbe9f88139b.png[/img]
A: [img=265x83]1802dbe9d991653.png[/img]
B: [img=241x83]1802dbe9e3d07e7.png[/img]
C: [img=250x83]1802dbe9ee13f79.png[/img]
D: [img=261x83]1802dbe9f88139b.png[/img]
举一反三
- 函数[img=216x83]180303a1b801632.png[/img]的反函数是( )。 A: [img=265x83]180303a1c31a037.png[/img] B: [img=241x83]180303a1cfbfa3b.png[/img] C: [img=250x83]180303a1d955469.png[/img] D: [img=261x83]180303a1e39cb77.png[/img]
- 函数[img=216x83]1803c80039dc82f.png[/img]的反函数是 A: [img=265x83]1803c8004430985.png[/img] B: [img=241x83]1803c8004ed4f53.png[/img] C: [img=250x83]1803c8005999c03.png[/img] D: [img=261x83]1803c80064b25b1.png[/img]
- 下列函数的导数[img=281x27]1802f62346026a9.png[/img] A: g'(x)=3 B: g'(x)=-3 C: g'(x)=9 D: g'(x)=-9
- 设随机变量X 和Y相互独立且都服从正态分布[img=61x27]180387e11b2d7af.png[/img],而[img=85x23]180387e123ff847.png[/img]和[img=76x23]180387e12c35f4e.png[/img]分别是来自总体X和Y简单随机样本,则统计量[img=136x51]180387e134c69e8.png[/img]服从的分布是( ) A: F(9, 9) B: t(9) C: F(1, 9) D: F(9, 1)
- 设随机变量X 和Y相互独立且都服从正态分布[img=61x27]180390b43a319ba.png[/img],而[img=85x23]180390b44248a66.png[/img]和[img=76x23]180390b44a902cc.png[/img]分别是来自总体X和Y简单随机样本,则统计量[img=136x51]180390b4539ab5f.png[/img]服从的分布是( ) A: F(9, 9) B: t(9) C: F(1, 9) D: F(9, 1)